Rituales y creencias funerarias en el centro poblado San Joaquín de Omaguas, provincia de Loreto, Nauta 2022 - Moscoso Villena, Claudia Patricia (2023)
The present investigation entitled "Rituals and funeral beliefs in the San Joaquín de Omaguas town center, province of Loreto - Nauta, 2022", took place in the San Joaquín de Omaguas town center, where the first indigenous people arrived in the province of Loreto. In this research we use the qualitative approach and the ethnographic method, we resort to the identification of key informants, among them leaders and wise men of the community, women, and older adults among others. At the same time, we apply data collection instruments, such as semi-structured interviews and information guides, which allow the reader to know, describe, interpret and relate funeral rituals and beliefs over time. The results of the research show that funeral beliefs and rituals have been having changes over time, practices are no longer like before but some traditions are still preserved. Adults and older adults are the main source for these beliefs and rituals to be transmitted to the youngest generation such as children and adolescents. The people have decided to maintain and revalue the customs that have been lost over time and to strengthen those customs that today no longer practice it.